Exploring Leadership Competencies and Mentoring Needs of Physical and Occupational Therapy Leaders in the United States - Rutschke, Mica; Fick, John (Journal of Health and Allied Sciences NU, 2023)
Study Design The current study used a phenomenological qualitative design to investigate leadership competencies and mentoring needs of physical and occupational therapy leaders.Objectives The purpose of the study was to evaluate leadership competencies of physical and occupational therapy leaders based on years of leadership experience and determine their mentoring needs for developing leadership competencies.Background Personnel shortages are a major issue in health care, and health care organizations should focus on professional development of health care leaders for better staff retention.Methods and Measures Nonprobability convenience sampling was used to recruit physical and occupational therapists currently working as therapy leaders in the United States. A self-developed, two-part structured interview guide was created and contained three demographic questions regarding leadership and four open-ended questions. Before the interview, participants reviewed the National Center for Healthcare Leadership Health Leadership Competency Model 3.0, which discusses seven domains of leadership competency, and the interview guide. Interviews took ∼30 to 45 minutes and were conducted using Zoom. NVivo software was used to code interviews for themes, and identified themes were grouped into five categories of years of leadership experience.Results Twenty-five physical and occupational therapists participated in the study. Participants in all five experience categories identified collaboration and communication as leadership competencies they possessed. Other identified competencies were analytical thinking, team leadership, accountability, and professional and social responsibility. Human resource management, financial skills, and relationship and network development were identified as mentoring needs for developing leadership competencies by participants in all categories. Information technology management and self-confidence were also identified.Conclusions By determining the current leadership competencies and mentoring needs, the results of the current study may be useful for establishing leaders who can address personnel shortages in health care.
Keywords: physical therapy leader; occupational therapy leader; leadership competencies; mentoring